Reposicionamento dos antidepressivos fluoxetina e paroxetina - Foletto, Vitória Segabinazzi (2022)
The substantial increase in multidrug resistant (MDR) bacteria makes efforts to find more effective antimicrobial therapies urgent. Drug repositioning, defined as the process of investigating new uses for drugs that have already been clinically approved, has offered a number of advantages in the face of the current lack of therapeutic innovations. As it is a faster, safer and more economical technique than the conventional development of active substances, repositioning has shown advantages. Also, synergism resulting from the combination of two or more drugs can improve drug efficacy, reduce toxicity, and provide an expanded spectrum of activity compared to monotherapeutic regimens. Thus, this study presents candidate drugs for redirection in bacterial infections and in the face of the pandemic caused by the new coronavirus (SARS-CoV-2). The present study investigated the biological activity of antidepressants belonging to the class of selective serotonin reuptake inhibitors (SSRIs) fluoxetine (FX) and paroxetine (PX). The analysis of antibacterial activity was performed in vitro using American Type Culture Collection (ATCC) standard bacterial strains and MDR clinical isolates, determining the minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), interaction with the antibacterial ceftriaxone (CTX) using the Checkerboard method and determination of the fractional inhibitory concentration index (FICI). It was observed that, against five ATCC standard strains and 72 MDR clinical isolates collected in 2019 and 2021 in a university hospital in southern Brazil, FX presented MIC values between 4 and 256 µg/ml, while PX ranged from 1 to 256 µg /ml. CTX, on the other hand, presented MIC ≥4096 µg/ml against most strains evaluated. The association of CTX with FX/PX using the Checkerboard method caused CTX to reduce the MIC by up to 32,000 times. FICI values < 0.5 against all strains tested ratified the synergism of the combination of drugs. FX and PX were also able to promote the cleavage of double-stranded plasmid DNA through a hydrolytic mechanism at the three concentrations tested, showing greater efficiency at pH 7,4 at 37 °C. Faced with SARSCoV-2, different studies have found that antidepressant drugs belonging to the class of SSRIs were able to reduce the risk of intubation or death related to Covid-19, reduce the need for intensive medical care, in addition to inhibiting viral titers in up to 99%. This means that, after additional studies, the repositioning of this class of drugs could be a promising alternative in the treatment of patients with Covid-19, especially fluoxetine and fluvoxamine. The antimicrobial activity of several non-antibiotic drugs belonging to different pharmacological classes was also systematically evaluated, in order to present probable candidates for repositioning in infectious diseases, especially antidepressant, antihypertensive, anti-inflammatory, antineoplastic, hypoglycemic drugs, among others. We conclude that drug repositioning is currently a promising approach against bacterial infections and in the fight against Covid-19, and that the antidepressants fluoxetine and paroxetine prove to be promising alternatives that have significant antibacterial and antiviral properties.